Analisis Akuntabilitas Laporan Pertanggungjawaban Dalam Pengelolaan Dana Bop Paud Pada Pemerintah Kota Tanjungpinang - Nurfitri Zulaika; Mayang Lestari; Budi Zulfachri; Andres Putranta Sitepu; Salihi Salihi (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
The purpose of this study is to find out how the management of the Operational Assistance for the Implementation of Early Childhood Education (BOP PAUD) funds and to determine whether the management of the Operational Assistance for the Implementation of Early Childhood Education (BOP PAUD) funds is accountable in accordance with applicable regulations. This research belongs to the type of qualitative research, namely research conducted by analyzing all the data used to determine the accountability of accountability reports in managing PAUD BOP funds at the Tanjungpinang City Government. The data used in this study are primary and secondary data. Data collection techniques used in this research are literature study, observation, interviews, and documentation. The data analysis used is qualitative analysis. The results showed that (1) the provision of PAUD BOP funds was in accordance with the BOP PAUD technical guidelines, (2) there were still some schools that did not follow the requirements in the PAUD BOP technical instructions to upload the number of students at the Dapo of PAUD Dikmas, (3) the allocation and the distribution of BOP PAUD funds is in accordance with the BOP PAUD technical instructions, (4) the use of PAUD BOP funds is in accordance with the BOP PAUD technical guidelines, (5) the reporting of PAUD BOP funds is not in accordance with the technical instructions because there are still PAUD institutions that are late in reporting accountability reports.